2006
DOI: 10.2119/2006-00039.gu
|View full text |Cite|
|
Sign up to set email alerts
|

Untitled

Abstract: During remodeling progress post myocardial infarction, the contribution of neoangiogenesis to the infarct-bed capillary is insufficient to support the greater demands of the hypertrophied but viable myocardium resulting in further ischemic injury to the viable cardiomyocytes at risk. Here we reported the bio-assay-guided identification and isolation of angiogenic tannins (angio-T) from Geum japonicum that induced rapid revascularization of infarcted myocardium and promoted survival potential of the viable card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The antiapoptosis effect may cause the restoration of blood supply or the initiation of the intracerebral revascularization. The effect of GJ extracts was also observed in the ischemic myocardium by Gu et al [ 47 ], who in their study has demonstrated that GJ extracts could promote the expression of angiogenic factors, restore early revascularization, and improve blood supply to ischemic myocardium. At the same time, it could also induce the expression of antiapoptotic protein Bcl-2 in infarcted hearts and inhibit the apoptosis of cardiomyocytes.…”
Section: Discussionmentioning
confidence: 64%
“…The antiapoptosis effect may cause the restoration of blood supply or the initiation of the intracerebral revascularization. The effect of GJ extracts was also observed in the ischemic myocardium by Gu et al [ 47 ], who in their study has demonstrated that GJ extracts could promote the expression of angiogenic factors, restore early revascularization, and improve blood supply to ischemic myocardium. At the same time, it could also induce the expression of antiapoptotic protein Bcl-2 in infarcted hearts and inhibit the apoptosis of cardiomyocytes.…”
Section: Discussionmentioning
confidence: 64%
“…Perfusion technique has been used to isolate endothelial cells of the heart especially from the coronary artery endothelial cells [ 6 – 11 ]. Magnetic bead cell sorting using single [ 12 ] or multiple markers [ 13 16 ] has been performed to purify endothelial cells from the heart. Flow cytometry has been used to sort cells after labeling with DiI-Ac-LDL [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%